Keragaman Kelapa Sawit Di Pasar Mostik Dan Internasional - Purba, Jan Horas Veryady (Jurnal Ilmiah Ranggagading (JIR), 2001)
The development in CPO farming sub sector has a strategy place in the national economic i.e. as one of the contributors to the stateâs foreign exchange. The research emphasizes the domestic analysis. Domestic analysis is aimed to un cover the factors uncover influencing Indonesiaâs production of CPO based, on regions and the business pattern, while global market analysis is aimed to find out the factor of Indonesiaâs and discovering Indonesiaâs position in international market. The research is continued with a simulation analysis to see the effects of some important variables domestic policies, and also to see the effect of many external factors (foreign) to Indonesiaâs CPO to variety